The variability of radio pulsars - Brook, P (2015)
Neutron stars are amongst the most exotic objects known in the universe; more than a solar mass of material is squeezed into an object the size of a city, leading to a density comparable to that of an atomic nucleus. They have a surface magnetic field which is typically around a trillion times stronger than the magnetic field here on Earth, and we have observed them to spin up to around 700 times per second. The existence of neutron stars was first proposed by Baade and Zwicky in 1934 but later graduated from theory to fact in 1967 as the first pulses were detected by Jocelyn Bell-Burnell, a then graduate student at the University of Cambridge. There are now well over 2000 neutron stars whose radio emission beams point at, and have been detected on Earth. We call these objects pulsars. Because of their remarkable properties, pulsars are very useful to physicists, who can employ them as precision timing tools due to the unwavering nature of their emission and of their rotation. Having an array of ultra-accurate clocks scattered throughout our galaxy is very useful for performing astrophysical experiments. In particular, precise pulsar timing measurements and the models that explain them, will permit the direct detection of gravitational radiation; a stochastic background initially, and potentially the individual signals from supermassive black hole binaries. Our models of pulsar behaviour are so precise that we are now able to notice even slight departures from them; we are starting to see that unmodelled variability in pulsars occurs over a broad range of timescales, both in emission and in rotation. Any unmodelled variability is, of course, detrimental to the pulsar's utility as a precision timing tool, and presents a problem when looking for the faint effects of a passing gravitational wave. We are hoping that pulsar timing arrays will detect gravitational radiation in the coming decade, but this depends, in part, on our ability to understand and mitigate the effects of the unmodelled intrinsic instabilities that we are observing. One important clue as to the nature of the variability in pulsar emission and rotation, is the emerging relationship between the two; we sometimes observe correlation on timescales of months and years. We have been observing pulsars for almost fifty years and our expanding datasets now document decades of pulsar behaviour. This gives us the ability to investigate pulsar variability on a range of timescales and to gain an insight into the physical processes that govern these enigmatic objects. In this thesis I describe new techniques to detect and analyse the emission and rotational variability of radio pulsars. We have employed these techniques on a 24 year pulsar dataset to unearth a striking new example of a dramatic and simultaneous shift in a pulsar's emission and rotation. We hypothesise that this event was caused by an asteroid interaction, although other explanations are also possible. Our variability techniques have also been used to analyse data from 168 young, energetic pulsars. In this thesis we present results from the nine most interesting. Of these, we have found some level of correlated variability in seven, one of which displays it very strongly. We have also assessed the emission stability of the NANOGrav millisecond pulsars and have found differing degrees of variability, due to both instrumental and astrophysical causes. Finally, we propose a method of probing the relationship between emission and rotation on short-timescales and, using a simulation, we have shown the conditions under which this is possible. Throughout the work, we address the variability in pulsar emission, rotation and links between the two, with the aim of improving pulsar timing, attaining a consolidated understanding of the diverse variable phenomena observed and elucidating the evolutionary path taken by pulsars.